The Effectiveness of Character-Integrated Quantum Learning on Students' Learning Motivation in Early Childhood Science Courses - Windayani, Ni Luh Ika; Widyasanti, Ni Putu (Universitas Pendidikan Ganesha, 2025)
The issue of low student motivation in early childhood science education courses has become a major concern in improving the quality of higher education, particularly in Early Childhood Teacher Education (PGPAUD) programs. This study aims to examine the effectiveness of the Quantum Learning model integrated with character values in enhancing students’ learning motivation. A quantitative approach was employed using a quasi-experimental method with a pretest-posttest control group design. The participants consisted of 60 PGPAUD students at STAHN Mpu Kuturan Singaraja enrolled in the early childhood science course. The sample was randomly divided into two groups: an experimental group that received instruction through the Quantum Learning model with embedded character values (n=30), and a control group that received conventional instruction (n=30). A validated learning motivation scale was used as the research instrument. Data were analyzed using Analysis of Covariance (ANCOVA). The results revealed a significant difference in posttest motivation scores between the experimental and control groups (p < 0.001), with a Partial Eta Squared value of 0.843, indicating a large effect size. Meanwhile, pretest scores did not significantly affect posttest outcomes (p > 0.103). It can be concluded that the Quantum Learning model integrated with character values is effective in increasing students’ learning motivation. These findings imply the importance of incorporating character education into instructional models to improve the quality of future early childhood educators.